Pregnancy outcomes after chemotherapy for trophoblastic neoplasia - GARCIA,MILA TREMENTOSA (2016)
SUMMARY Introduction The successful development of chemotherapy enabled a fertilitysparing treatment for patients with trophoblastic neoplasia. After disease remission, the outcome of a subsequent pregnancy becomes a great concern for these women. Objective To analyze existing studies in the literature that describe the reproductive outcomes of patients with trophoblastic neoplasia treated with chemotherapy. Method Systematic review was performed searching for articles on Medline/ Pubmed, Lilacs and Cochrane Library databases, using the terms “gestational trophoblastic disease” and “pregnancy outcome”. Results A total of 18 articles were included. No evidence of decreased fertility after chemotherapy for trophoblastic neoplasia was observed. The abortion rates in patients who conceived within 6 months after chemotherapy was higher compared to those who waited longer. Some studies showed increased rates of stillbirth and repeat hydatidiform moles. Only one work showed increased congenital abnormalities. Conclusion The pregnancies conceived after chemotherapy for trophoblastic neoplasia should be followed with clinical surveillance due to higher rates of some pregnancy complications. However, studies in the literature provide reassuring data about reproductive outcomes of these patients.